The Microsoft Multiperson Location Survey - Krumm, John; Horvitz, Eric (2005)
The Microsoft Multiperson Location Survey (MSMLS) is an ongoing research project aimed at surveying the travel patterns of regular people. We loan to our volunteer subjects a GPS receiver capable of measuring and storing time-stamped (latitude, longitude) data. Nominally, we expect our subjects to leave the GPS in their car for about two weeks, during which time the GPS will record everywhere the car goes. When the subject returns the GPS, we upload the stored data to our server. With this data we are pursuing research projects for generating efficient driving directions and predicting a driver’s destination. This evolving technical report describes the project and the data gathered so far.